The Ku Klux Klan in Mississippi: a history - Newton, Michael (McFarland & Company)
"Since 1866 the Ku Klux Klan has been a significant force in Mississippi, enduring repeated cycles of expansion and decline. Klansmen have rallied, marched, elected civic leaders, infiltrated law enforcement, and committed crimes. It details its complete history, campaigns of terrorism, KKK involvement in politics and religion, and its role as a social movement for marginalized poor whites"--Provided by publisher